2019
DOI: 10.15252/embj.201899748
|View full text |Cite
|
Sign up to set email alerts
|

Human Fis1 regulates mitochondrial dynamics through inhibition of the fusion machinery

Abstract: Mitochondrial dynamics is important for life. At center stage for mitochondrial dynamics, the balance between mitochondrial fission and fusion is a set of dynamin‐related GTP ases that drive mitochondrial fission and fusion. Fission is executed by the GTP ases Drp1 and Dyn2, whereas the GTP ases Mfn1, Mfn2, and OPA 1 promote fusion. Recruitment of Drp1 to mitochondria is a critical step in fission. In yeast, Fis1p recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(164 citation statements)
references
References 84 publications
(181 reference statements)
5
159
0
Order By: Relevance
“…Moreover, the authors show that the effects of Fis1 overexpression on mitochondrial morphology are suppressed by latrunculin B. Actin assembly between ER and mitochondria is known to play an important role during Drp1‐dependent fission. The results of Yu et al () now suggest that Fis1 also contributes to mitochondrial dynamics in an actin‐dependent, but Drp1‐independent manner. It remains to be seen whether these actions of Fis1 also occur at the MAM or elsewhere.…”
Section: The Dual Role Of Fis1 In Mitochondrial Morphologymentioning
confidence: 88%
See 4 more Smart Citations
“…Moreover, the authors show that the effects of Fis1 overexpression on mitochondrial morphology are suppressed by latrunculin B. Actin assembly between ER and mitochondria is known to play an important role during Drp1‐dependent fission. The results of Yu et al () now suggest that Fis1 also contributes to mitochondrial dynamics in an actin‐dependent, but Drp1‐independent manner. It remains to be seen whether these actions of Fis1 also occur at the MAM or elsewhere.…”
Section: The Dual Role Of Fis1 In Mitochondrial Morphologymentioning
confidence: 88%
“…In this context, Yu et al () focused on answering the question: Why Fis1 overexpression can still induce fragmentation in the absence of Drp1? They first tested the domains within Fis1 required to induce Drp1‐independent fragmentation and found that the presence of both cytosolic and transmembrane domains of Fis1 is required for fragmentation.…”
Section: The Dual Role Of Fis1 In Mitochondrial Morphologymentioning
confidence: 99%
See 3 more Smart Citations